2019
DOI: 10.1038/s41598-019-49025-z
|View full text |Cite
|
Sign up to set email alerts
|

Ensuring access to high-quality resources reduces the impacts of heat stress on bees

Abstract: Pollinators are experiencing declines globally, negatively affecting the reproduction of wild plants and crop production. Well-known drivers of these declines include climatic and nutritional stresses, such as a change of dietary resources due to the degradation of habitat quality. Understanding potential synergies between these two important drivers is needed to improve predictive models of the future effects of climate change on pollinator declines. Here, bumblebee colony bioassays were used to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 90 publications
0
71
0
Order By: Relevance
“…In the field, bumblebees may regularly experience differences in the nutritional quality of their resources (Vanderplanck et al 2014). Poor nutritional quality alters foraging activity (Pankiw et al 2004) and influences physiological conditions (Stabler et al 2015), whereas high-quality diets could have a buffering effect of heat stress on colonies (Vanderplanck, Martinet et al 2019). In other insects such as fruit flies or beetles, feeding raises CT max by increasing the body mass of the organism or by improving nutritional or hydration status (Nyamukondiwa & Terblanche 2009;Chidawanyika et al 2017).…”
Section: Heat Resistance and Body Massmentioning
confidence: 99%
“…In the field, bumblebees may regularly experience differences in the nutritional quality of their resources (Vanderplanck et al 2014). Poor nutritional quality alters foraging activity (Pankiw et al 2004) and influences physiological conditions (Stabler et al 2015), whereas high-quality diets could have a buffering effect of heat stress on colonies (Vanderplanck, Martinet et al 2019). In other insects such as fruit flies or beetles, feeding raises CT max by increasing the body mass of the organism or by improving nutritional or hydration status (Nyamukondiwa & Terblanche 2009;Chidawanyika et al 2017).…”
Section: Heat Resistance and Body Massmentioning
confidence: 99%
“…In addition to the direct effects of climate change on species distributions, climate change might also increase the chance of losing appropriate floral resources by differentially altering the phenology of bees and plants and increasing temporal mismatches between them (Schleuning et al 2016;Ogilvie and Forrest 2017). Though our understanding of this phenomenon is largely theoretical and based on model predictions, empirical work suggests that access to high-quality resources can mitigate the impact of heat stress (Vanderplanck et al 2019).…”
Section: Response To a Changing Climatementioning
confidence: 99%
“…To minimize the impact of heat stress on localized populations, we support the establishment of multiple and connected highquality habitat to improve bumblebee conservation (Vray 2018). It has been shown that highquality resources can mitigate the effect of heat stress (Vanderplanck et al 2019). Our study also raises a question about the use of a single bumblebee species in studies focusing on environmental stressors (i.e., nutritional stress, pesticides, parasites).…”
Section: Bumblebee Conservationmentioning
confidence: 91%